Impact of Agricultural Communication Interventions on Improving Agricultural Productivity in Malawi - Fallys Masambuka-Kanchewa; Mary T. Rodriguez; Emily Buck; Jera Niewoehner-Green; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2020)
Agricultural communication (AGCOM) has been known to aid in disseminating research-based agricultural information among Malawian farmers. In 1958 the Malawi Government, via the Ministry of Agriculture, established the Agricultural Communications Branch (ACB) in an attempt to increase access to and adoption of scientifically-proven technologies among farmers. Moreover, in 2000 the Malawi Government started implementing an agricultural extension policy that promoted pluralistic demand-driven extension, which led to the increased availability of non-governmental organizations providing AGCOM services to farmers. However, after several decades of using different communication tools to promote new technologies, low productivity in most small holder farms remains a challenge, with limited adoption of improved technology as one of the contributing factors. In this exploratory, convergent, mixed methods study, 30 Malawian farmers and six AGCOM officers who were selected using convenient and snow ball sampling respectively participated in key informant interviews. In addition, 64 AGCOM officers who were selected using simple random sampling were involved in a survey. The findings of the study revealed that information delivered to farmers does not address farmer needs in most cases. Specifically, existing policies, source and availability of funding, and the agricultural calendar influenced choice of information that was disseminated. For example,the existing policy does not allow AGCOM officers to disseminate local and innovative farmer practices unless they are tested and approved by scientists. Such policies, perpetuates a mindset among farmers that innovations originate from outside their communities, thereby making it hard for them to share their local, indigenous ideas with their colleagues. Moreover, it has contributed to the inability of AGCOM to be used as an innovation creation tool, hence AGCOMs’ limited impact.
Keywords: adoption; improved technologies; agricultural communication; increased productivity; information dissemination